Aspergillus section Versicolores: nine new species and multilocus DNA sequence based phylogeny - Z. Jurjevic; S.W. Peterson; B.W. Horn (IMA Fungus)
β-tubulin, calmodulin, internal transcribed spacer and partial lsu-rDNA, RNA polymerase 2, DNA replication licensing factor Mcm7, and pre-rRNA processing protein Tsr1 were amplified and sequenced from numerous isolates belonging to Aspergillus sect. versicolor. The isolates were analyzed phylogenetically using the concordance model to establish species boundaries. Aspergillus austroafricanus, A. creber, A. cvjetkovicii, A. fructus, A. jensenii, A. puulaauensis, A. subversicolor, A. tennesseensis and A. venenatus are described as new species and A. amoenus, A. protuberus, A. sydowii, A. tabacinus and A. versicolor are accepted as distinct species on the basis of molecular and phenotypic differences. PCR primer pairs used to detect A. versicolor in sick building syndrome studies have a positive reaction for all of the newly described species except A. subversicolor.